Efektivitas Penerapan Smart System Dukcapil dalam Pelayanan Administrasi Digital di Kota Palangka Raya - Aldo Yanuarto; Aji Santoso; Lia Amelia; Ahmad Rusdie Nur Fadillah; Ardian Ari Prnata5; Muhammad Ramadhan; Muza Muza; Kamal Hasuna; Reza Noor Ikhsan (Lembaga Pengembangan Kinerja Dosen, 2025)
Digital transformation in public service is an inevitable necessity in the era of modern governance. This study aims to analyze the effectiveness of the implementation of the Smart Civil Registration System (Smart System Dukcapil) in digital administrative services in Palangka Raya City as part of the national e-government initiative and the strengthening of electronic-based governance. The research employs a qualitative descriptive method, collecting data through in-depth interviews, direct observations, and document analysis of relevant regulations and the implementation of the system within the Department of Population and Civil Registration (Disdukcapil) of Palangka Raya City.The findings indicate that the implementation of the Smart System Dukcapil through applications such as the Sistem Informasi Dukcapil Oloh Itah (SI-DOI) and Digital Population Identity (IKD) has significantly improved efficiency, transparency, and data accuracy in population administration services. These digital innovations have streamlined bureaucratic processes, minimized physical interaction, and enhanced public satisfaction with administrative services. However, the system’s effectiveness is still constrained by challenges such as limited internet infrastructure in peripheral areas, low digital literacy among citizens, and inadequate technical capacity among civil servants in operating digital systems optimally. Theoretically, the implementation of the Smart System Dukcapil reflects the realization of good governance and smart governance principles through the integration of technology, bureaucratic reform, and community participation. This study recommends strengthening human resource capacity, expanding digital infrastructure, and promoting continuous public education to ensure system sustainability. Consequently, digital population administration in Palangka Raya has the potential to become an innovative, inclusive, and adaptive model for regional public service governance.